Search 70,573 tutors

# 3a2-ab3+5 for a=5 and b=2

the 2 by the a is meant to be a to the power of 2 or squared and the 3 by the b is meant to be b to the power of 3 or b cubed

3a2-ab3+5 for a=5 and b=2

Substitute 5 for every "a" you see and 2 for every "b" you see

3(5)^2 - (5)(2)^3 + 5 = 3(5 * 5) - 5(2 * 2 * 2) + 5

Use your order of operations - PEMDAS

3(25) - 5(4 * 2) + 5 = 75 - 5(8) + 5 = 75 - 40 + 5 35 + 5 = 40

3a^2-ab^3+5 for a=5 b=2

so substitute

3(5^2)-(5*(2^3))+5

PEMDAS

3(25)-(5*8)+5

solve

75-40+5=40   Ans.=40

for every "a", replace it with 5. and for every "b" replace it with 2. then you get:

3(5)^2 - 5(2)^3+5

order of operations (Parenthesis, Exponents, Multiply or divide (right to left) , Add or Subtract (right to left) says do the powers first

3(25) - 5(8) +5

then multiply

75 - 40 + 5

75 - 40 = 35 + 5 = 40

Kenton,

So then you have 3(5)^2 - (5)(2)^3 +5

which reduces to

3(25) - 5(8) + 5

and gives

75-40+5 =

you can do the rest i'm sure

Hope this helps!

Art